The Explosion in Grandma’s Attic, the Cabinet of Curiosities, and Chance Encounters at the GLBT History Museum - de Szegheo Lang, Tamara (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2015)
This article proposes that objects might be instrumental in museum exhibitions that promote critical thinking around issues of human rights and social inequity. Objects have the potential to present histories that have been marginalized for far too long and to get away from rehearsed narratives, while also engaging the visitor through emotional connection — making the visitor care about the histories that are being presented. In looking at the GLBT Historical Society Archives and History Museum in San Francisco, this article claims that new museums that grow out of community-based archives might provide the opportunity for the kinds of critical engagements with objects that national-scale museums that attempt to address social problems often do not have. Specifically addressing the GLBT History Museum’s inaugural exhibit, “Our Vast Queer Past,” this article argues that the organization of objects on display, greatly influenced by their archival roots, gives viewers the opportunity for chance encounters with histories that come to matter to them.